Epidemiological characteristics of cerebral palsy in children and adolescents in a Brazilian northeast capital (Fisioterapia e Pesquisa, 2020)
This study aimed to describe the prevalence of cerebral palsy among children and adolescents, its subtypes, associated comorbidities, and socioeconomic characteristics of families. This is a cross-sectional epidemiological study conducted from a population-based survey on cerebral palsy among children and adolescents in the city of Aracaju, Sergipe, Brazil. Results: Based on guardians’ answers to the proposed questionnaire, we obtained data on 240 children and adolescents with cerebral palsy in Aracaju. The period prevalence of cerebral palsy was 1.37 per 1,000 people. Some neighborhoods showed a prevalence three to four times higher than that found to the overall city, indicating that the total prevalence is not a homogeneous indicator. Most participants were male (56.25%), self-declared as mixed-race or Black (67.50%), and aged 8.56 years on average. Bilateral spastic was the most prevalent cerebral palsy subtype (45.42%), and epilepsy was the most common comorbidity (48.33%) along with intellectual disability. Household monthly income was $ 252.87. Our results indicate that children and adolescents with cerebral palsy are mostly from minoritized groups, Black or mixed-race, and live in extreme poverty.